Kontekstualisasi Asketisme Max Weber dalam Masyarakat Islam Moderen di Indonesia - Offy Resdiantari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This article aims to analyze the asceticism thoughts conveyed by Max Weber and contextualize them into the order of modern Islamic society in Indonesia. The method in this study applies a qualitative research design through library study. The data for this study were obtained from a collection of essays written by Max Weber entitled The Protestant Ethic and The Spirit of Capitalism as well as secondary literature written by other authors to sharpen the elaborative analysis in this study. The results of this study indicate that worldly asceticism conveyed by Max Weber can influence the socio-economic actions of modern Islamic society in Indonesia. Modern Islamic society in Indonesia–represented by the Islamic organizations Muhammadiyah, Persis, and Al-Irsyad establish and implement Islamic principles that correlate with worldly asceticism. This can be seen from the existence of the organization's vision and mission that rationalizes the practice of Islamic teachings through a social theological approach that is realized through the establishment of Islamic schools, hospitals, and orphanages. Thus, this article contributes to broadening the interpretive horizon regarding the relevance of Weber's thinking in the context of religion and culture.